Tangibilización del espíritu emprendedor: desarrollo de franquicias en el sector de la pequeña y microempresa - Gastañaduy Benel, Alfonso (2009)
When talking about economic development in emerging countries, it is generally stressed the role of micro and small enterprises (MSE), both for its ability to generate employment and for being the manifestation of the entrepreneurial spirit of its managers. For them is clearing the way and create practical options to maximize the results of their work. It is with this philosophy that this document raises the importance of the corporate franchises system as a mean to optimize the performance of MSE. And how can we have evidence of such optimization? There can be many ways, but the concept that is becoming more important is how to make tangible the corporate work, which means how to make «touchable» the entrepreneurial spirit, the very critical resource for managing the MSE. This is the message: the franchises make tangible the entrepreneurship spirit of the MSE.